PENGARUH PEMUTARAN VIDEO TERHADAP PEMERIKSAAN PAYUDARA SENDIRI (SADARI) PADA REMAJA PUTRI DI PANTI ASUHAN AL AKBAR PEKANBARU - Kursani, Elmia; Roviola, Roviola; Purwanti, Yuni; Sari, Yusmita; Khadijah, Putri (Ensiklopedia of Journal, 2023)
Adolescence is a period of transition from childhood to adulthood, where there is dynamic and rapid growth and development both physically, psychologically, intellectually and socially, which is related to puberty. Problems related to adolescent reproductive health include breast cancer and cervical cancer. The most common type of cancer that occurs in women is breast cancer. This is influenced by the low awareness and knowledge of young women to carry out early detection such as BSE. The purpose of this study was to determine the effect of using video media on knowledge of early detection of breast cancer in young women at the Al Akbar Orphanage in Pekanbaru. The design of this study was an experiment using a quasy experimental design, using a Non-randomized Pretest–Posttest Control Group Design. The results showed that there was an increase in knowledge of young women at the Al Akbar orphanage after being given knowledge about breast cancer and BSE using video media through the results of an effectiveness test with the dependent t-test, where the P-value was 0.009 <0.05. This means that there is a significant difference in the level of knowledge between before and after being given the BSE video. The conclusion of the study showed that there was an effect of the intervention providing knowledge about BSE and breast cancer through playing the BSE video on increasing respondents' knowledge before and after the BSE video playback intervention.Keywords: Examination, BSE, Video Media, Knowledge, Teenage girl